Thermal study of Fe3O4/blood and CoFe2O4/blood magneto nanofluids study over an exponential surface inspired by convective heating and radiations - Yassine Bouazzi; Adnan; Sami Ullah Khan; Mutasem Z. Bani-Fwaz; Dana Mohammad Khidhir; Tadesse Walelign; Mohamed Bechir Ben Hamida (Scientific Reports)
Abstract This work examines the role of Fe3O4/blood and CoFe2O4/blood nanofluids across an exponential surface associated to magnetic field, thermal radiation, and convective heating. It provides better thermal conductivity, biomedical application (such as drug targeting for treatment), and excellent efficiency of heat transfer, significant for the hyperthermia treatment and new hemodynamic systems. Thus, a bionanofluid model under mentioned physical constraints through an exponential surface is modeled. The formulation leads to a nonlinear mathematical model with enhanced characteristics of bionanofluid which then investigated numerically for physical responses of the parameters. It is examined that thermal efficiency of Fe3O4/blood is higher than CoFe2O4/blood due to strengthening the concentration and radiation effects. Intensive magnetic field and convective heating provided considerable thermal improvement in Fe3O4/blood and CoFe2O4/blood which point towards the use of Fe3O4 as a reliable option for magnetic hyperthermia and controlled thermal treatment in biomedical systems. Further, the shear drag in CoFe2O4/blood diminishes rapidly than Fe3O4/blood due to enhanced magnetic field and stretching of the surface. The outcomes demonstrate the applicability of Fe3O4 to areas where efficient heat transfer is demanded in biomedical or thermal applications.